2019
DOI: 10.3389/fpsyg.2019.01761
|View full text |Cite
|
Sign up to set email alerts
|

A Population Study of Relative Age Effects on National Tests in Reading Literacy

Abstract: We examined relative age effects (RAE) in national test results in reading literacy in Norway in 2013, in Grades 5, 8, and 9 students ( n = 173,421) to estimate how month of birth is associated with mean scores and different achievement levels. The results confirm that there is an approximately linear decrease in test scores across months of birth for all grades and both genders. Consequently, students born early in the year are more likely to end up at higher achievement levels than stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Students born in January had up to 15% greater average scores than their peers born in December of the same year, with the greatest differences in Grade 5 (Aune et al, 2018). The same researchers (Aune et al, 2017(Aune et al, , 2018Vestheim et al, 2019) also found differences in relation to gender. In marks in physical education (Aune et al, 2017) and in scores on the national test of numeracy, boys born early in the year were overrepresented among high-performing students (Aune et al, 2018), whereas Vestheim et al (2019) found that girls were overrepresented among high-performing students in reading literacy in Grades 5 and 9.…”
Section: Introductionmentioning
confidence: 84%
See 2 more Smart Citations
“…Students born in January had up to 15% greater average scores than their peers born in December of the same year, with the greatest differences in Grade 5 (Aune et al, 2018). The same researchers (Aune et al, 2017(Aune et al, , 2018Vestheim et al, 2019) also found differences in relation to gender. In marks in physical education (Aune et al, 2017) and in scores on the national test of numeracy, boys born early in the year were overrepresented among high-performing students (Aune et al, 2018), whereas Vestheim et al (2019) found that girls were overrepresented among high-performing students in reading literacy in Grades 5 and 9.…”
Section: Introductionmentioning
confidence: 84%
“…Thus, both their gender and their birthdate would be associated with a developmental lag compared with their peers. As discussed in the introduction of this paper, boys are known to be overrepresented in a host of populations with developmental problems ( Root et al, 2019 ), as well as to receive poorer marks than girls (e.g., Statistics Norway, 2009 ; Aune et al, 2017 , 2018 ; Vestheim et al, 2019 ). The same holds for children born late in the year, as has been demonstrated in a plethora of studies on the RAE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the sport domain, relative younger individuals may counter the RAE if they are more maturational advanced [21,33], while there is substantial variability in effect sizes for RAEs observed in PE, from small to large [7,[28][29][30]. Additionally, RAEs are previously found for numeracy and reading literacy [34,35], where maturity associated physical advantages should be of no importance. This highlights the independent nature of these two constructs, with separate factors underlying biological maturity and relative age.…”
Section: Plos Onementioning
confidence: 99%
“…Donolato (2019) also argued that the influence of the home environment on children's reading is important, and they suggested that children's relationship with reading begins to develop before they start school, and that home facilitation has a similar role to the development of intentional reading in kindergarten [19]. Vestheim (2019) confirmed that test scores at each grade level decreased approximately linearly between birth months [20]. Yuan-Hsuan et al (2013) examined the effects of two types of online reading activities on reading literacy through mediation analysis based on metacognitive strategy knowledge [21].…”
Section: Introductionmentioning
confidence: 99%